Impulsive mathematical modeling of ascorbic acid metabolism in healthy subjects. (7th March 2016) - Bachar, Mostafa; Raimann, Jochen G.; Kotanko, Peter
Abstract: In this work, we develop an impulsive mathematical model of Vitamin C (ascorbic acid) metabolism in healthy subjects for daily intake over a long period of time. The model includes the dynamics of ascorbic acid plasma concentration, the ascorbic acid absorption in the intestines and a novel approach to quantify the glomerular excretion of ascorbic acid. We investigate qualitative and quantitative dynamics. We show the existence and uniqueness of the global asymptotic stability of the periodic solution. We also perform a numerical simulation for the entire time period based on published data reporting parameters reflecting ascorbic acid metabolism at different oral doses of ascorbic acid. Abstract : Highlights: We have developed a mathematical model allowing the prediction of ascorbic acid dynamics at different states of vitamin C intake. In addition to intestinal uptake, distribution and dynamics in the extracellular volume and the tissue, we have also included a novel approach to quantify the glomerular excretion of ascorbic acid. We also analyzed the global asymptotic stability of acid kinetics model in healthy subjects.